Trees For Food Security-2 Project, Rwanda Highlights - Ndayambaje, J.D.; Mukuralinda, Athanase; Njoki, C.; Niyitanga, F.; Bambe, J.C.; Kinuthia, R.; Kuria, A.; Muthuri, Catherine W. (World Agroforestry Centre, 2021)
The ‘Developing integrated options and accelerating scaling up of agroforestry for improved food security and resilient livelihoods in Eastern Africa’ project also known as Trees for Food Security phase 2 (T4FS-2) is an Australian Centre for International Agricultural Research (ACIAR) funded project aimed at improving food security and smallholder livelihoods through the widespread implementation of appropriate locally adapted agroforestry practices in key agricultural landscapes of Rwanda, Uganda and Ethiopia.